سير الخصومة التحكيمية التجارية الدولية في التشريع الجزائري - عبير قيدوم; خولة بن علجية (My University, 2021)
Abstruct: The process of adjudicating arbitration begins with the expression of one of the parties to the dispute about its desire to start the arbitral proceedings through a request submitted to the other party with the aim of submitting the dispute to the arbitral tribunal , and the arbitration dispute is governed by the principle of willpower , as it is subject to the agreement of the parties in all its phases from the formation of the arbitral tribunal and the determination of the law applicable to this dispute leading to the issuance of the final ruling in the dispute. The algerian legislator has dealt with the arbitration system within the civil and administrative procedures law and stipulated most of the rules regulating the arbitration process , starting with the formation of the arbitration court , passing through the recognition and implementation of the arbitral award issued by the arbitral tribunal , up to appeal this rulling , although it neglected some aspects of its internal law , but it redressed the situation by joining and ratifying many agreements international which included the issue of arbitration in its varios aspects. .................. الملخص: تبدأ عملية السير في الخصومة التحكيمية بتعبير أحد أطراف النزاع عن رغبته في بدء الإجراءات التحكيمية عن طريق طلب يقدمه إلى الطرف الآخر بهدف عرض النزاع على الهيئة التحكيمية ، و خصومة التحكيم يحكمها مبدأ سلطان الإرادة ، حيث تخضع لإتفاق الأطراف في جميع مراحلها بدءا من تشكيل الهيئة التحكيمية و تحديد القانون الواجب التطبيق على هذه الخصومة ، وصولا لإصدار الحكم النهائي الفاصل في النزاع ، و قد تناول المشرع الجزائري نظام التحكيم ضمن قانون الإجراءات المدنية و الإدارية و نص على أغلب القواعد المنظمة لعملية التحكيم بدءا من تشكيل محكمة التحكيم مرورا بالإعتراف و تنفيذ الحكم التحكيمي الصادر عن الهيئة التحكيمية وصولا إلى الطعن في هذا الحكم ، و إن كان قد أغفل بعض الجوانب في قانونه الداخلي لكنه تدارك الوضع بانضمامه و مصادقته على العديد من الإتفاقيات الدولية التي نضمت مسألة التحكيم بمختلف جوانبها. ....................... Résumé : Le processus de règlement d’un différend arbitral commence par le fait qu’une partie exprime son désir d’engager une procédure arbitrale par le biais d’une demande à l’autre partie aux fins de soumettre le différend au tribunal arbitral et le différend arbitral est régi par le principe de l’autorité de volonté, comme il est soumis à l’accord des parties à toutes les étapes de la formation du tribunal arbitral à la détermination de la loi applicable au présent litige Le législateur algérien a traité le système d’arbitrage dans le cadre du Code de procédure civile et administrative et stipulait la plupart des règles régissant le processus d’arbitrage, de la formation du tribunal arbitral à la reconnaissance et à l’exécution du jugement du tribunal arbitral à l’appel de ce jugement. et s’il omet certains aspects de son droit interne mais remédie à la situation en adhérant et en ratifiant plusieurs conventions internationales qui ont incorporé la question de l’arbitrage dans ses divers aspects.